Metal-free regioselective cross dehydrogenative coupling of cyclic ethers and aryl carbonyls - Mane, Kishor D.; Mukherjee, Anagh; Vanka, Kumar; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2019)
A highly regioselective, efficient, and metal-free oxidative cross dehydrogenative coupling (CDC) of aryl carbonyls with cyclic ethers has been developed. This method offers easy access to substituted alpha-arylated cyclic ethers with a high functional group tolerance in good to excellent yields. The regioselectivity of this CDC reaction was confirmed by density functional theory (DFT)-based calculations.